Disparities Among Districts in Central Java Province: Cluster Analysis Based on Several Well-Being Indicators - Dewi Agita Pradaningtyas; Tityas Margawati; Joni Trisetio Putro (Jurnal Ekonomi Pembangunan, 2022)
This paper aims to group districts in Central Java Provinces based on several well-being indicators published by The National Statistics Agency of Indonesia (BPS) in 2019. The Ward method used hierarchical cluster analysis to group districts and identified disparities among clusters. The results show that districts in Central Java can be divided into 3 clusters: cluster 1 consists of 4 sections with a high level of well-being; cluster 2 consists of 16 districts with a moderate level of well-being; and cluster 3 consists of 15 districts with the low level of well-being. The average variable score for each cluster indicates disparities among groups. The variable score for cluster 1 with the high level of well-being is far above the score for clusters 2 and 3 in economics, education, sanitation, and public health. Only four districts belong to the cluster with a high level of well-being, all of which have administrative status as a city. In contrast, communities with a low level of well-being all have a managerial position as regencies. The results also found that districts in the western part of Central Java tend to have a lower level of well-being than the eastern part of Central Java. Thus, Central Java Province needs to pay more attention to districts in cluster 3 with a low level of well-being, especially in the western part of Central Java in terms of economy, education, sanitation, and public health.